Increasing Competency in Writing Review through Problem Based Learning (PBL) Models - Sutrisno, Sutrisno (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The purpose of this classroom action research to: (1) describe the learning process with a problem-based learning model (PBL) to improve the writing competency of students in class XI MIPA 5 students in SMAN 1 Bantul in the academic year 2019/2020 and (2) knowing the increase in writing competency in student reviewer writing grade XI MIPA 5 SMAN 1 Bantul 2019/2020 school year through a problem based learning model (PBL). The subjects of this study were students of class XI MIPA 5 SMAN 1 Bantul. In the school Year 2019/2020. The setting/location of the study was in SMAN 1 Bantul Yogyakarta. While the research time was for three months from January to March 2020. This class action research was conducted in two cycles. Each cycle consists of four activities, namely: (1) action planning, (2) action implementation, (3) observation, and (4) reflection. The results of this class action research show: (1) The Problem Based Learning Model (PBL) can improve teacher performance in learning, improve student performance in learning, and obtain excellent responses from students; and (2) The implementation of PBL learning models in learning can improve the competency of writing a review of students.